Diagnosing and Managing Linear Scleroderma in a Low-Resource Setting - Sreyleak Luch; Pauravy Men; Gwenyth Fischer; Andrew Wu (Case Reports in Pediatrics, 2023)
Background. Linear scleroderma is one of the five forms of scleroderma, but it is the most common form of localized scleroderma in childhood. If left untreated, it can lead to severe disfigurement and functional impairment. The typical appearance is a linear streak with cutaneous induration on the face or head in association with various ophthalmological and neurological signs and symptoms. Treatment typically includes corticosteroids and/or methotrexate with life-long monitoring for recurrence. Case Presentation. A 12-year-old girl presented to our clinic in northern rural Cambodia with a history of a linear streak on her forehead that was growing down her nasal bridge. She denied any tenderness or family history of rheumatic disease. Her history was significant for strabismus as a child. A visiting pediatric rheumatologist assisted us with the appropriate diagnosis and treatment plan. Conclusion. In our case report, we present a child with linear scleroderma who fortunately came to medical attention early and received appropriate treatment before the onset of complications. She was treated with systemic immunosuppression as well as topical steroids. After treatment, she had no further progression on her face and continued to follow up with us to monitor for disease activity. To summarize, linear scleroderma is an uncommon diagnosis for general pediatricians and should be recognized early to provide appropriate treatment and follow-up.